2018
DOI: 10.1007/s00253-018-9111-5
|View full text |Cite
|
Sign up to set email alerts
|

Chlorination caused a shift in marine biofilm niches on microfiltration/ultrafiltration and reverse osmosis membranes and UV irradiation effectively inactivated a chlorine-resistant bacterium

Abstract: The effect of chlorine disinfection on marine biofilm populations and communities formed on membrane surfaces was investigated under two feedwater conditions: raw seawater and deep bed filtration-treated seawater. As a result of chlorination, the structure of the biofilm community on the microfiltration/ultrafiltration and reverse osmosis membrane coupons shifted significantly at the genus level. However, the total bacterial population was not reduced under the two feedwater conditions. This failure to control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Ultrafiltration membranes can be used to separate colloids, macromolecular organic compounds, and suspended solids, and are widely used to clarify feed liquids, separate, and purify macromolecular organic compounds, and remove sources of heat. Cho et al (2018) reported that the structure of the biofilm community on the microfiltration/ultrafiltration and reverse osmosis membrane coupons shifted significantly at the genus level. Campos et al (2010) studied the ultrafiltration peptides of cowpea protein extract hydrolysate, and the results showed that the hydrolysates and ultrafiltration peptides can be used to prepare physiological functional foods with antihypertensive and antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafiltration membranes can be used to separate colloids, macromolecular organic compounds, and suspended solids, and are widely used to clarify feed liquids, separate, and purify macromolecular organic compounds, and remove sources of heat. Cho et al (2018) reported that the structure of the biofilm community on the microfiltration/ultrafiltration and reverse osmosis membrane coupons shifted significantly at the genus level. Campos et al (2010) studied the ultrafiltration peptides of cowpea protein extract hydrolysate, and the results showed that the hydrolysates and ultrafiltration peptides can be used to prepare physiological functional foods with antihypertensive and antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%